Preliminary Research: Utilization of Gourami Fish Bone Flour (Osphronemus gouramy) in Making Calcium Dumplings - Dwi Lestari Handayani; Monicha Efi Sumaimi; Tri Ani Ashari; Jumadi Jumadi (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
Highlight • Knowing the amount of daily calcium needed • Knowing utilization of fish bone meal and its processed products • Analysis of the most preferred types of food and fish species